Systematic review of sourcing and 3D printing: make-or-buy decisions in industrial buyer–supplier relationships - Matthias M. Meyer; Andreas H. Glas; Michael Eßig (Management Review Quarterly, 2020)
Additive manufacturing (AM) is regarded as a technology that has transformative and disruptive potential in nearly all industries. However, AM is not only about new production equipment and processes. Given the decreasing degree of vertical integration in many companies, suppliers add significant value to the finished product. AM might lead to the redesign of production networks, including a scenario in which the buyer uses AM to produce parts with data provided by suppliers. Overall, AM could have a major impact on the ways in which buyers and suppliers collaborate in the future. Nevertheless, research on AM in the field of industrial procurement remains scarce. This is surprising, given that AM is not only changing traditional procurement categories and creating new ones (comprising printers, powder raw materials, data and the associated engineering services) but AM's widely discussed potential for decentralisation might also restructure the logistical aspects (transport, stocks) of supply chains. In addition, AM may resurrect the old procurement question of `make or buy'. Current research focuses on the logistical aspects of AM and concerns such issues of decentralisation (such as the diminishing need for transportation and the design of transport networks). In contrast, this research addresses the question of whether AM demands new answers to strategic sourcing questions. For this purpose, academic journal literature concerning procurement and AM search strings is reviewed. Selected articles are analysed using a fine-grained analytical framework of procurement strategies. The findings show that existing research lacks theoretical approaches and a systematic view of the topic. Specifically, the analysis reveals a number of distinct knowledge gaps, which present several potential directions for future research.
Keywords: M11; L24; L14; 650; Procurement; Sourcing; Strategy; Additive manufacturing; 3D printing; Systematic literature review